2011
DOI: 10.1111/j.1365-313x.2011.04484.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional implication of the MYB transcription factor RVE8/LCL5 in the circadian control of histone acetylation

Abstract: SUMMARYDespite our increasing understanding of the molecular determinants essential for circadian clock function, we still lack a complete picture of the mechanisms contributing to clock progression in plants. Here, we explore the role of REVEILLE8/LHY-CCA1-LIKE5 (RVE8/LCL5) within the Arabidopsis circadian system. RVE8/LCL5 encodes a MYB-like transcription factor similar to CIRCADIAN CLOCK-ASSOCIATED1 (CCA1) and ELONGATED HYPOCOTYL (LHY), which are essential regulators of the Arabidopsis circadian clock. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
180
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(188 citation statements)
references
References 47 publications
7
180
0
1
Order By: Relevance
“…Two MYB transcription factors antagonistically contribute to this regulation. At dawn, CCA1 represses TOC1 expression by promoting histone deacetylation, whereas REV-EILLE 8/LHY-CCA1-LIKE 5 acts as an activator and facilitates histone acetylation (31,32). A recent report has extended this analysis showing that CCA1 and LHY are also subjected to rhythmic changes in H3 acetylation and methylation (33).…”
mentioning
confidence: 69%
“…Two MYB transcription factors antagonistically contribute to this regulation. At dawn, CCA1 represses TOC1 expression by promoting histone deacetylation, whereas REV-EILLE 8/LHY-CCA1-LIKE 5 acts as an activator and facilitates histone acetylation (31,32). A recent report has extended this analysis showing that CCA1 and LHY are also subjected to rhythmic changes in H3 acetylation and methylation (33).…”
mentioning
confidence: 69%
“…In a recent study, we have characterized the implication on the Arabidopsis circadian system of RVE8/LCL5, a MYB-like transcription factor with a high degree of sequence homology to CCA1. 6 By using RVE8/ LCL5 overexpressing and mutant plants, we found that RVE8/LCL5 binds to the TOC1 promoter and contributes to proper circadian expression of TOC1. Our studies also show that in contrast to CCA1, RVE8/LCL5 seems to favor H3 acetylation, most likely by antagonizing CCA1 the TOC1 locus are important for TOC1 circadian expression, 5 we next examined whether mis-expression of RVE8/LCL5 affected the pattern of H3 acetylation at the TOC1 promoter.…”
Section: Histone Acetylation and The Circadian Clockmentioning
confidence: 99%
“…However, the module also showed enrichment toward "circadian rhythm" and "long-day photoperiodism, flowering" (GO:0007623 and GO:0048574, respectively). These two predictions are particularly interesting, as the module contains LHY-CCA1-LIKE5 (LCL5), encoding a MYB family TF that was only known to be involved in response to hormone stimuli but has recently been experimentally assigned to both "photoperiodism, flowering" and "circadian rhythm" (Farinas and Mas, 2011). Next to the newly assigned MYB LCL5, the module contains two more MYB TF genes (REVEILLE1 [RVE1] and CIRCADIAN1 [CIR1]).…”
Section: ) No Bp Information Was Known For Anac073mentioning
confidence: 99%